Il mondo finisce a Rio: «Demônios» di Aluísio Azevedo (Altre Modernità, 2013)
This essay analyses Demônios, a short story by the Brazilian writer Aluísio Azevedo published in 1893 in a collection bearing the same title. The text – unrelated to the naturalistic production of the author – describes a catastrophic nightmare, a carioca apocalypse reverting the evolutionary process and affecting the only two survivors, whose lives revert until they dissolve themselves in an aerial entity floating in the space. While trying to fit such an extravagant work within the production of its author, I will also explore the connection between the end of the world narrated by Azevedo as a positivist and a republican and the events involving the Brazilian republic in the early 1890s.